The development of outgroup contact - Pfister, M (2020)
Decades of intergroup contact research have highlighted the beneficial effect of outgroup contact on outgroup attitude measures. However, there is a need to add a complementary perspective focused on increasing outgroup contact (i.e., behaviour) as improved attitude measures do not always translate into outgroup contact. While research has started to explore the development of outgroup contact, there is a need for more and better research in that direction. The present thesis addresses this paucity of research and provides an additional step towards filling this gap further by addressing when and how the development of outgroup contact over time can be facilitated. Chapter 1 provides an overview of the theoretical and empirical foundation of this thesis. Next, in three empirical chapters, I focus on the development of outgroup contact in adolescence in England, Germany, The Netherlands, and Sweden by using longitudinal social network survey and intervention data. Chapter 2 explores the relationship between contact capacity and the development of outgroup contact and finds that individuals’ level of existing contact is associated with less outgroup (and ingroup) contact. Chapter 3 considers self-esteem as a mediator in the relationship between perceived discrimination and the development of outgroup contact, whereby perceived discrimination reduces individuals’ self-esteem, which, in turn, reduces the development of outgroup contact. Chapter 4 introduces an intergroup contact intervention programme aimed at facilitating the development of outgroup contact and reports that individuals who (indirectly) participate in the programme develop more outgroup contact over time in comparison to individuals without exposure to the intergroup contact intervention. Finally, Chapter 5 summarises and discusses the findings of this thesis and further addresses its implications. Overall, the presented research in this thesis highlights the importance of outgroup contact development in intergroup contact research and advocates strongly for a more profound examination of the development of outgroup contact to assess the effectiveness of outgroup contact in increasingly diverse societies.